(untitled) (Práxis Educativa, 2013)
The quality of undergraduate teaching, seen from the point of view of teacher selection, teaching and research is the discussion proposed by this study. Research was carried out with university teachers at the beginning of their teaching career. A historical survey was developed about the selection of teachers for higher education, emphasizing culture and values present in each period; and results of a study carried out with twenty-seven teachers from four Brazilian universities are presented. Data was collected through semi-structured interviews which allowed the teachers to reveal their views on quality from the work they develop. Results highlight that the comprehension of quality by the interviewees pointed to different understandings and in them it is possible to perceive the values they consider important in undergraduate teaching. Keywords: Teaching quality. Beginner teachers. Higher Education.